Digital Literature Competency Training For English Teachers Based On E-Learning Moodle - Razak, Yusuf; Hasbi, Muhammad; Satriani; Huda, Nabila; Muzkiyah, Nurul (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
The teaching and learning process at all levels of education must continue in the period of the COVID-19 epidemic that is currently sweeping the globe. Both offline and online, a variety of learning methods and tools are employed. Online learning is still limited, and rigorous health standards must be followed. In the meantime, online learning is a viable option. Many online media, such as Google Classroom, WA Group, Zoom, Cisco Webex, Google Duo, and others, can be used. This community service intends to assist teachers in improving their Moodle application skills. It is now the most feature-rich online (distance) learning program available. The teachers were very engaged in this activity throughout the activation process, from socialization to training, as indicated by the large number of invited participants who all showed up. Participants attended the training from beginning to end, actively participated in the training, and the Teacher submitted numerous questions and concerns. Participants used the Moodle application to learn English online after completing the training. Some teachers use their classroom time to create educational materials, online conversations, quizzes, and assignments, as well as to ask questions and motivate students.